High-Temperature Measurements of Materials - Fukuyama, Hiroyuki (Springer, 2017)
Thermophysical properties of high-temperature materials are important from both the scientific and engineering points of view. This book includes the latest developments in the measurements of atomic structure, density, surface tension, viscosity, heat capacity, thermal and mass diffusivity, thermal conductivity, emissivity, and electrical conductivity of mainly metallic melts. High-temperature measurements are difficult due to high chemical reactivity and fluidity. Some distinctive inventions on the experimental techniques such as levitation technique combined with microgravity, synchrotron radiation or magnetic field enable high-precision measurements. This book is the perfect choice for specialists and nonspecialists eager to know the cutting-edge details in this field.